Electing amateur politicians reduces cross-party collaboration - Rachel Porter; Jeffrey J. Harden; Mackenzie R. Dobson (Proceedings of the National Academy of Sciences, 2025)
Public trust in democratic institutions has dropped to historic lows, prompting electorates in major democracies to turn to “amateur” politicians with the expectation that these political outsiders will cut through stalemates to deliver policy results. Amateurs are often seen as pragmatic “doers,” but also uncompromising, a combination at odds with governing systems where legislative progress depends on cross-party coalitions. Using the US Congress as a critical case, we evaluate these competing expectations by linking over four decades of election data with 2.2 million bill (co)sponsorship records. We find that electing amateurs intensifies partisan divisions: Districts that send amateurs to Congress yield representatives who attract fewer opposing-party collaborators to their bills and less often support other-party legislation. Our results suggest that amateurs are unlikely to deliver on their promise for pragmatic governance, as they resist or undervalue the compromises essential to lawmaking.